FAKTOR-FAKTOR PENDORONG DAN PENARIK YANG MENYEBABKAN PENDUDUK SUKU BANTEN BERMIGRASI - Refda Niari; Buchori Asyik; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2013)
This research aim to analyze The pushing and the interesting Factors that cause resident of banten ethnic group migrate to sukajawa village, west tanjung karang subdistrict, Bandar lampung city year 2012. This research used descriptive method. The sample of this research are all of the patriarch of banten ethnic group who migrate to sukajawa village. Which is the total amount is 67 patriaches. The data taking is done by observation technique, interview, documentation and questionare. Data is analyzed by tabulation percentage technique as a basic interpretation and description to give the meaning of data that is used as the result of this research. The result find of this research, we can infer that the cause of why resident of banten ethnic group migrate to sukajawa village is because there are the pushing and interesting factors that influence the patriarch to do migration. In pushing factors, stated that 1) about the business field in original place, 2) about the income in original place. On the other hand, especially in interesting factors, 1) stated that location of destination place is easy to reach, 2) about there is hope about better economic status in destination place, 3) about the easy to get the working chance in destination place and the last stated that there is an offering of friend or their relative in destination place as an interesting factors they do the migration. Key words: Faktors, the cause , migrate